Hypersensitive C-reactive protein-atherogenic index as a novel marker for metabolic dysfunction-associated steatotic liver disease in type 2 diabetes mellitus - Wang, Wei; Chen, Yan Ying; Guo, Xiu Li; Tong, Yan (Frontiers in Endocrinology, 2025)
BackgroundHypersensitive C-reactive protein-atherogenic index (CAI) may serve as a novel marker for metabolic dysfunction-associated steatotic liver disease (MASLD) in type 2 diabetes mellitus (T2DM). This study aimed to evaluate the association between CAI and MASLD risk, while comparing its diagnostic performance with C-reactive protein-triglyceride glucose index (CTI), triglyceride-glucose (TyG) index, and atherogenic index of plasma (AIP).MethodThe final cohort included 1,071 individuals with T2DM from the Metabolic Management Center of our hospital. The association between CAI and MASLD was assessed by the binomial logistic regression, restricted cubic splines (RCS), and subgroup analysis. Receiver operating characteristic curve analysis was performed to evaluate the diagnostic performance of CAI for MASLD, with DeLong analysis used to compare its diagnostic ability to CTI, TyG index, and AIP.ResultsIndividuals in the higher CAI quartiles demonstrated a greater prevalence of MASLD (P < 0.05). After adjusting for confounding factors, CAI was independently associated with a higher risk of MASLD (OR: 2.14, 95% CI: 1.74-2.62, P < 0.001). Each SD increase in CAI was associated with a 99% higher risk of MASLD (OR: 1.99, 95% CI: 1.65-2.39, P < 0.001). These associations persisted across subgroups of sex, anti-hepatic steatosis hypoglycemic agent, hypertension, alcohol consumption, and statin use (all P < 0.05). RCS analysis revealed a linear association between CAI and risk of MASLD (P for nonlinearity = 0.357). ROC analysis indicated that CAI had a diagnostic ability for MASLD (AUC:0.732, 95%CI:0.702-0.762), outperforming CTI (AUC difference: 0.020, 95% CI: 0.007-0.034, P = 0.003), TyG (AUC difference: 0.044, 95% CI: 0.026-0.062, P < 0.001), and AIP (AUC difference: 0.022, 95% CI: 0.011-0.033, P < 0.001) in the DeLong analysis.ConclusionThe CAI could serve as a novel marker for screening high-risk populations for MASLD in T2DM.